Acute enhancement of necrotic radio‐frequency ablation lesions in left atrium and pulmonary vein ostia in swine model with non‐contrast‐enhanced T1‐weighted MRI. Issue 4 (30th September 2019) - Guttman, Michael A.; Tao, Susumu; Fink, Sarah; Tunin, Rick; Schmidt, Ehud J.; Herzka, Daniel A.; Halperin, Henry R.; Kolandaivelu, Aravindan
Abstract : Purpose: To evaluate non‐contrast‐enhanced MRI of acute radio‐frequency ablation (RFA) lesions in the left atrium (LA) and pulmonary vein (PV) ostia. The goal is to provide a method for discrimination between necrotic (permanent) lesions and reversible injury, which is associated with recurrence after treatment of atrial fibrillation. Methods: Fifteen normal swine underwent RFA around the right‐superior PV ostia. Electrical pulmonary vein isolation (PVI) was verified by electro‐anatomic mapping (EAM) and pacing. MRI was carried out using a 3D respiratory‐gated T 1 ‐weighted long inversion time (TWILITE) sequence without contrast agent. Key settings were: inversion time 700 ms, triggering over 2 cardiac cycles, pixel size 1.1 mm 3 . Contrast‐enhanced imaging and T 2 ‐weighted imaging were carried out for comparison. Six animals were sacrificed on ablation day for TTC‐stained gross pathology, 9 animals were sacrificed after 2–3 mo after repeat EAM and MRI. Image intensity ratio (IIR) was used to measure lesion enhancement, and gross pathology was used to validate image enhancement patterns and compare lesion widths. Results: RFA lesions exhibited unambiguous enhancement in acute TWILITE imaging (IIR = 2.34 ± 0.49 at 1.5T), and the enhancement patterns corresponded well with gross pathology. Lesion widths in MRI correlated well with gross pathology ( R 2 = 0.84), with slight underestimation by 0.9 ± 0.5 mm. Lesion enhancement subsided chronically. Conclusion: TWILITE imaging allowed acute detection of permanent RFA lesions in swine LA and PV ostia, without the need for contrast agent. Lesion enhancement pattern showed good correspondence to gross pathology and was well visualized by volume rendering. This method may provide valuable intra‐ or post‐procedural assessment of RFA treatment.